An experimental study using a sexual strategies explanation to reduce homophobia toward gay men among lay people and healthcare professionals in China - Gao, Qianhui; Antfolk, Jan; Santtila, Pekka (Frontiers in Psychology, 2023)
Introduction Homophobic discrimination and stigmatization, especially from healthcare professionals, are important stressors for gay men. Homophobia may be partly rooted in seeing some gay men having casual sex and many sexual partners as a signal of mental problems. Sexual Strategies Theory (SST) suggests that such sexual behavior is a result of different sexual strategies men and women tend to adopt and is unrelated to sexual orientation per se. This study aimed to investigate (1) the effectiveness of providing an SST explanation for gay men’s sexual behavior in reducing homophobia among both lay persons and healthcare professionals; (2) differences in homophobia between healthcare professionals and lay people and also between medical and non-medical professionals. Methods The main analyses included 492 heterosexual participants recruited online via Chinese social media and sample services in 2021. Of these, 227 were healthcare professionals (128 medical, 99 non-medical) and 265 were lay people. The participants were randomly assigned into an experimental group given the SST explanation (n = 126), an active control group given a Minority Stress (MS) explanation (n = 184), and a control group (n = 182). After the manipulation, homophobia, knowledge about homosexuality, professional homophobic attitude, gay affirmative practice, and contact with gay men were assessed. Results The results of factor analysis suggested dividing homophobia into Oppressing Homophobia (Oppressing HP) describing believing that gay men should have fewer rights and Pathologizing Homophobia (Pathologizing HP) describing believing that the sexual behavior of gay men is a signal of mental problem. Importantly, the SST explanation reduced Pathologizing HP while the MS explanation reduced Oppressing HP. Healthcare professionals reported more Oppressing HP than lay people, and medical professionals conducted less gay affirmative practice than non-medical professionals. Conclusion An SST explanation can potentially reduce some aspects of homophobia among both healthcare professionals and lay people. Also, worryingly, Chinese healthcare professionals, especially medical professionals, reported more homophobia than lay individuals.